2015
DOI: 10.1088/0953-8984/27/16/166003
|View full text |Cite
|
Sign up to set email alerts
|

Magnon Hall effect on the Lieb lattice

Abstract: Ferromagnetic insulators without inversion symmetry may show magnon Hall effect (MHE) in the presence of a temperature gradient due to the existence of Dzyaloshinskii-Moriya interaction (DMI). In this theoretical study, we investigate MHE on a lattice with inversion symmetry, namely the Lieb lattice, where the DMI is introduced by adding an external electric field. We show the nontrivial topology of this model by examining the existence of edge states and computing the topological phase diagram characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…The associated magnon bands in the magnetically ordered systems have a nontrivial topology with Chern number protected chiral magnon edge modes in two-dimensional (2D) systems and magnon surface states in three-dimensional (3D) systems. They are dubbed topological magnon Chern insulators [3][4][5][6][7][8][9] and Weyl magnons [10][11][12][13] respectively. They are the analogs of electronic topological (Chern) insulators [14][15][16] and Weyl semimetals [17][18][19].…”
mentioning
confidence: 99%
“…The associated magnon bands in the magnetically ordered systems have a nontrivial topology with Chern number protected chiral magnon edge modes in two-dimensional (2D) systems and magnon surface states in three-dimensional (3D) systems. They are dubbed topological magnon Chern insulators [3][4][5][6][7][8][9] and Weyl magnons [10][11][12][13] respectively. They are the analogs of electronic topological (Chern) insulators [14][15][16] and Weyl semimetals [17][18][19].…”
mentioning
confidence: 99%
“…Seminal papers showed that interesting effects in condensed matter systems [14][15][16] are observed. Additionally, the influence of the singularity of flat band systems was investigated in the frame of the fractional quantum and magnon Hall effect [17,18] and energy localization in the presence of magnetic fields [19], spin-orbit coupling [20,21], or disorder [22,23]. Recently this topic attracted a lot of attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of Kerr nonlinearity in the system may exhibit conical diffraction at the Dirac cone [30,34]. Due to their simple geometry, Lieb lattices are in the focus of research in ultracold systems as an optical trap for fermions [35], providing existence of magnon Hall effect in spite of the presence of inversion symmetry [18], protection and formation of robust zero modes localized at point defects [36], optimization of the BCS critical temperature and superfluid weight [37], and lifting the flat band modes by PT-symmetric perturbation due to thresholdless PT-symmetry breaking [38]. Moreover, it has been shown that the Lieb lattice acts as a good platform for analyzing various topological transitions in Chern insulators [20,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…A rapidly developing field is the extension of topological concepts to nonelectronic bosonic systems such as magnons [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and phonons [31][32][33][34][35][36][37][38][39]. Unlike electronic systems these bosonic quasi-particles are chargeneutral which makes them potential candidates to design systems with low-dissipation and good coherent transport applicable to spin-based computing and magnon spintronics [40].…”
Section: Introductionmentioning
confidence: 99%